Transformasi Digital dalam Strategi Branding UMKM Lokal: Studi Kasus Dodol Betawi di Kabupaten Bekasi - Sandi Yuda, Mulfi; Afrizal Maulana, Mochamad; Muchsam, Yoki; Wahyu Akbar, Tri Sanatha; Raspati, Galih (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
Traditional SMEs based on local culture face significant challenges in adopting digital transformation, particularly in developing adaptive branding strategies in the digital economy era. This research addresses the urgency of bridging the digital literacy gap and cultural understanding in the marketing strategies of Betawi dodol SMEs in Bekasi Regency. The primary objective of this study is to analyse how local entrepreneurs understand, adopt, and implement digital branding within the social and cultural context of Betawi. The research methodology employs a qualitative approach with an intrinsic case study, utilising semi-structured interviews, participatory observation, and visual documentation of Betawi dodol entrepreneurs in Ceger. The research findings indicate that the digital transformation of these SMEs remains sporadic, has not been structured as a comprehensive branding strategy, and relies more on social relationships and product quality. Brand identity is built organically through consumption experiences and local cultural values. The implications of this research highlight the importance of community-based mentoring and strengthening digital branding literacy rooted in local wisdom as a strategy for sustainable SME empowerment.